Negara, Ideologi Dan Pendidikan Islam: Kebijakan Negara Dalam Memperkuat Ideologi Islam Moderat - Bagas Mukti Nasrowi (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Abstract : This paper aims to reveal the state policy in instilling moderate Islamic ideology to its citizens through education, by examining the education system in several countries. In Indonesia, the state tries to form moderate Muslims in a relatively 'subtle' way, namely through the inculcation of the basis and ideology of the state (Pancasila and the 1945 Constitution) into all aspects of education, including through the establishment of the basis and function of religious education, the obligation to study Pancasila and PAI. (which is designed to produce moderate Muslims). The government of Turkey and Singapore has taken a different approach, which seems to be frontal and firm. In these two secular countries, the strategy of realizing moderate Muslims is carried out by controlling educational institutions, especially Islamic educational institutions, both formal educational institutions (schools and universities) and non-formal (such as Friday sermons, religious lectures, books, and magazines).